The association between dietary fat quality and quantity and hospitalization duration in COVID-19 in Iranian patients: a cross-sectional study - Shiraseb, Farideh; Mirzababaei, Atieh; Mehri Hajmir, Mahya; Ebrahimi, Sara; Hosseini, Shabnam; Zarrinvafa, Zeinab; Sadid, Mahnaz; Aali, Yasaman; Mohamadi, Azam; Mirzaei, Khadijeh (Frontiers in Nutrition, 2025)
BackgroundThe global impact of Coronavirus Disease 2019 (COVID-19 (has highlighted the necessity of understanding factors influencing its severity and hospitalization duration. While a balanced diet is crucial for immune support, the role of dietary fats in this context has not been well understood. This study explored associations between the quality and quantity of fatty acids and severity and the length of hospitalization in COVID-19 patients in 2022.MethodThis cross-sectional study included 107 COVID-19 patients aged 20–60 years who were hospitalized at Amir Alam Hospital in Tehran, Iran. Dietary fat intake was assessed using 24 h food recall. Data on symptoms were collected using a demographic questionnaire and verified against their hospital records. Linear and binary logistic regressions were employed for statistical analysis.ResultA higher omega 6/omega 3(N6/N3) ratio was linked to increased odds of respiratory distress syndrome (RDS) and elevated D-dimer levels, while correlating with lower odds of fever. While RDS odds increased over Vit E/polyunsaturated fatty acid (PUFA) ratio tertiles, chills decreased. [PUFA + monounsaturated fatty acid (MUFA)]/saturated fatty acid (SFA) ratio was associated with reduced odds of chest pain, duration of hospitalization (DH) time, c-reactive protein (CRP), and D-dimer levels. Furthermore, PUFA intake was negatively associated with odds of poor appetite, RDS, and headaches, whereas SFA intake was positively associated with odds of fever. Additionally, there was a positive correlation between cholesterol-saturated index (CSI) levels and DH time (P < 0.7).ConclusionOur findings indicate that higher N6/N3 and VitE/PUFA ratios were associated with increased RDS and D-dimer levels, while the VitE/PUFA ratio was linked to reduced chills. Higher (PUFA + MUFA)/SFA ratios were associated with lower chest pain, DH, CRP, and D-dimer levels. While higher PUFA intake was related to reduced poor appetite, RDS, and headache, higher SFA intake was linked to increased fever. Additionally, there was a positive association between CSI levels and DH. Current findings indicate that the quality and balance of dietary fats may play a crucial role in modulating inflammatory responses and clinical outcomes.